2015
DOI: 10.1071/ah14037
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-associated infections in Australia: time for national surveillance

Abstract: Objective. Healthcare-associated infection (HAI) surveillance programs are critical for infection prevention. Australia does not have a comprehensive national HAI surveillance program. The purpose of this paper is to provide an overview of established international and Australian statewide HAI surveillance programs and recommend a pathway for the development of a national HAI surveillance program in Australia.Methods. This study examined existing HAI surveillance programs through a literature review, a review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 43 publications
(49 reference statements)
0
22
0
Order By: Relevance
“…In Europe and North America, it is estimated that 12%-32% of infections associated with blood lead to death. However, the exact burden of HAI in each country is not yet known [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe and North America, it is estimated that 12%-32% of infections associated with blood lead to death. However, the exact burden of HAI in each country is not yet known [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, it has been estimated 175,000 cases of HAIs occur annually [8]. In Europe and North America, it is reported that 12-32% of HAI blood steam infections result in death [9]. However, the exact burden of HAI in each country is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although many countries have well established coordinated national healthcare associated infection (HAI) surveillance programs, Australia does not. In the absence of clear national direction, the separate evolution of Australia's eight States and Territories individual surveillance programs, which were gradually implemented during the 1990's and 2000's, (1) has resulted in methodology differences that have not been well understood. (1-3) Recently HAI surveillance has been mandated in the National Safety and Quality Health Service Standards for Australian Hospitals.…”
Section: Introductionmentioning
confidence: 99%